Synthesis and applications of polysubstituted bicyclo[1.1.0]butanes - McNamee, RE; Thompson, AL; Anderson, EA (American Chemical Society, 2021)
Bicyclo[1.1.0]butanes (BCBs) are valuable substrates in the “strain release” synthesis of polysubstituted four-membered ring systems, with applications including bioconjugation agents. The introduction of substituents onto the BCB bridges is challenging due to limitations in current methods for the preparation of this bicyclic scaffold, typically necessitating linear syntheses with limited functional group tolerance and/or substituent scope. Here, we report the synthesis of tri- and tetrasubstituted BCBs via directed metalation of readily accessed BCB amides; this straightforward “late stage” approach generates a wide variety of bridge-substituted BCBs that can be easily converted into other useful small ring building blocks. Access to a monodeuterated BCB afforded unprecedented insight into the mechanism of dihalocarbene insertion into BCBs to afford bicyclo[1.1.1]pentanes (BCPs).